Modified adaptive bats sonar algorithm with doppler effect mechanism for solving single objective unconstrained optimization problems - N. A., Azlan; Nafrizuan, Mat Yahya (Universiti Malaysia Pahang, 2019)
A modified adaptive bats sonar algorithm with Doppler Effect (MABSA-DE) is a new algorithm with an element of Doppler Effect theory that helped the transmitted bats’ beam towards a superior position. The performances of the proposed algorithm is validated on a several well-known single objective unconstrained benchmark test functions. The obtained results show that the algorithm can perform well to find optimum solution. The statistical results of MABSA-DE to solve all the test functions also has been compared with the results from the original MABSA on similar test functions. The comparative study has shown that MABSA-DE outperforms the original algorithm, and thus, it can be an efficient alternative method in solving single objective unconstrained optimization problems.